Gênero e envelhecimento ativo: a produção do ser mulher – um estudo sobre o SUPERA – curso de Ginástica para o Cérebro unidade de Francisco Beltrão-PR - Jacondino, Dóris Helena Voss (2021)
The active aging of women in the production of a new cultural identity is a latent theme in contemporary times. The increase in life expectancy and the destandardization of some female behaviors led women to assume new roles in the current social structure. As well as occupying public spaces, more specifically in the educational environment. The study will focus on SUPERA (Francisco Beltrão's Brain Gymnastics course). The aim of the research presented is to understand how the subjective production of women living active aging in FRANCISCO Beltrão's SUPERA is processed. The specific objectives are: to identify how women over 60 years of age live the process of active aging; to describe memories that go back to the processes of subjectivation experienced by older women throughout their life histories; to analyze the ways in which the production of female gender interrelated to aging occur among the research subjects. The central question of the research was defined as follows: is the subjective production of women living active aging in SUPERA – Gymnastics Course for the brain – Francisco Beltrão unit? The authors who gave theoretical and methodological support to the work were: Zanello (2018), Foucault (1996, 2006), Balandier (1999), Elias (1998), Izquierdo (1988), Butler (1999) and Silva (2005, 2010). As for the results, the analyses indicated the production of female identities interrelated to active aging in two ways: in subjectivation practices marked by the care of others, times lived in childhood, youth and adult life in which women devoted themselves primarily to domestic work, care for children and husbands and the home, evidencing to assume a gender position prevailing at that time by patriarchal culture. And, in a second moment, subjectivation practices marked by self-care, when a profound transformation is noticeable when prioritizing their own individual interests and desires, possibilities for active and healthy aging.